Calculating and communicating ensemble‐based volcanic ash dosage and concentration risk for aviation. (6th December 2018) - Prata, Andrew T.; Dacre, Helen F.; Irvine, Emma A.; Mathieu, Eric; Shine, Keith P.; Clarkson, Rory J.
Abstract : During volcanic eruptions, aviation stakeholders require an assessment of the volcanic ash hazard. Operators and regulators are required to make fast decisions based on deterministic forecasts, which are subject to various sources of uncertainty. For a robust decision to be made, a measure of the uncertainty of the hazard should be considered, but this can lead to added complexity preventing fast decision‐making. A proof‐of‐concept risk‐matrix approach is presented that combines uncertainty estimation and volcanic ash hazard forecasting into a simple warning system for aviation. To demonstrate the methodology, an ensemble of 600 dispersion model simulations is used to characterize uncertainty (due to eruption source parameters, meteorology and internal model parameters) in ash dosages and concentrations for a hypothetical Icelandic eruption. To simulate aircraft encounters with volcanic ash, trans‐Atlantic air routes between New York (JFK) and London (LHR) are generated using time‐optimal routing software. This approach was developed in collaboration with operators, regulators and engine manufacturers; it demonstrates how an assessment of ash dosage and concentration risk can be used to make fast and robust flight‐planning decisions, even when the model uncertainty spans several orders of magnitude. The results highlight the benefit of using an ensemble over a deterministic forecast and a new method for visualizing dosage risk along flight paths. The risk‐matrix approach is applicable to other aviation hazards such as sulphur dioxide (SO2 ) dosages, desert dust, aircraft icing and clear‐air turbulence, and is expected to aid flight‐planning decisions by improving the communication of ensemble‐based forecasts to aviation. Abstract : The methodology described in the present paper shows how a dispersion model ensemble can be used to make fast and robust flight‐planning decisions during volcanic eruptions. It was found that agreement between ensemble member simulations can be used to visualize confidence in ash concentration and dosage forecasts. The risk‐matrix approach allows for fast decision‐making, even when there is significant spread within the ensemble. Ash concentration and dosage risk are visualized along air routes for the first time.